Penerapan Aspek Environmental Dalam Arsitektur Sustainable Pada Perancangan Stasiun Kereta Api Pekanbaru - Muhammad Rafi Ihsan (Prodi Arsitektur Universitas Matana, 2021)
Pekanbaru is one of the big cities in Indonesia with a high population mobility. However, the city is not accompanied by the provision of fast and economical public transportation. The common public transportation facilities which are available in Pekanbaru, namely buses and travel, are considered as a quite economical, but require a long time to travel. Meanwhile, other transportation facilities, namely planes, are considered fast but less economical. Therefore, an economical and fast alternative public transportation, namely train, is needed. To meet this need, a railway station is required in Pekanbaru. The development condition in Pekanbaru which are getting faster and denser can adversely affect the environment. So, environmentally friendly and sustainable development is needed in the form of station designs that meet environmental aspects in sustainable architecture. The research method used is qualitative in the form of field data collection and literature study related to the topic of discussion.